2000
DOI: 10.1111/j.1574-6941.2000.tb00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse, yet-to-be-cultured members of the Rubrobacter subdivision of the Actinobacteria are widespread in Australian arid soils

Abstract: Phylogenetic analyses of ribosomal RNA gene sequences (rDNAs) retrieved from an Australian desert soil sample (Sturt National Park) revealed the presence of a number of clones which branched deeply from the high GC Gram-positive division line of descent. The most abundant group of these clones were related to Rubrobacter. An oligonucleotide probe was designed to have broad specificity to Rubrobacter and relatives. This probe was used to interrogate eight rDNA libraries representing four distinct land forms wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 26 publications
2
54
0
Order By: Relevance
“…The majority (74%) of Actinobacteria sequences identified in this study belong to the deepest branch of the phylum, the Rubrobacteridae, which are common in arid soils and on rock surfaces worldwide and are extremely resistant to desiccation and UV stress (Holmes et al, 2000;Rainey et al, 2005). The involvement of Rubrobacteridae in soil aggregate formation and calcite precipitation suggests that they may also be involved in engineering the soil surface structure during biocrust formation (Mummey and Stahl, 2004;Rainey et al, 2005;Mummey et al, 2006;Pellerin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The majority (74%) of Actinobacteria sequences identified in this study belong to the deepest branch of the phylum, the Rubrobacteridae, which are common in arid soils and on rock surfaces worldwide and are extremely resistant to desiccation and UV stress (Holmes et al, 2000;Rainey et al, 2005). The involvement of Rubrobacteridae in soil aggregate formation and calcite precipitation suggests that they may also be involved in engineering the soil surface structure during biocrust formation (Mummey and Stahl, 2004;Rainey et al, 2005;Mummey et al, 2006;Pellerin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous members of the Gram-positive, high-G þ C content Actinobacteria phylum are drought resistant and have been shown to be able to grow under challenging dry conditions (Goodfellow and Williams, 1983;Zvyagintsev et al, 2007). Nevertheless, the Rubrobacteridae class, which is abundant at our sites as well as in other waterlimited soils, remains poorly characterised (Holmes et al, 2000;Placella et al, 2012). In contrast with the Actinobacteria phylum, the Acidobacteria and Verrucomicrobia phyla do not appear to invest in ribosome accumulation during desiccation, but to rely on extremely rapid ribosomal synthesis upon rewetting.…”
Section: Bacterial and Fungal Community-level Responsementioning
confidence: 99%
“…Several , mg/g clones from this study are related to Rubrobacter species with a 94-95% sequence similarity. Rubrobacter have been isolated both in soils and thermal waters [Carreto et al, 1996;Chen et al, 2004;Saul et al, 2005;Suzuki et al, 1988], and Rubrobacter species have been found to be widespread in arid Australian soils [Holmes et al, 2000] and arid Antarctic soils [Aislabie et al, 2006]. The most well studied Rubrobacter species is radiotolerans with an ability to survive a 25kGy dose of radiation [Ferreira et al, 1999].…”
Section: Colony Forming Units (Cfu)mentioning
confidence: 99%